Development of an NLP-Based Communication Manual for Classroom Guidance Services in Junior High School - Rizki Erdiantoro; Yuli Nurmalasari (Ma'soem University, 2025)
Effective communication is a key element in the success of school counseling services, particularly in classroom guidance, which is delivered in group settings to students in the classroom. Unfortunately, many school counselors still apply one-way communication patterns that limit active student participation. This study aims to develop an effective Neuro-Linguistic Programming (NLP)-based communication guide for junior high school counselors to implement classroom guidance services. The research method used is Research and Development (R&D), adapted from the Borg & Gall model (1983) and modified to include only the expert and user validation stages. Data were collected through literature reviews, interviews, and the distribution of validation instruments to experts and prospective users, including school counselors. The result of the development is a guidance manual that includes the basic concepts of NLP, communication strategies, and their application in classroom-based counseling services. Validation results indicate that the developed guide is feasible, useful, and well-targeted. This study offers practical contributions by providing pedagogical tools that support school counselors’ communication skills through a systematic, applicable approach. The findings recommend NLP as an innovative approach to foster a more interactive communication climate within classroom guidance sessions.